T. gondii RP promoters & knockdown reveal molecular pathways associated with proliferation and cell-cycle arrest. - Samuel L Hutson; Ernest Mui; Karen Kinsley; William H Witola; Michael S Behnke; Kamal El Bissati; Stephen P Muench; Brittany Rohrman; Susan R Liu; Robert Wollmann; Yuko Ogata; Ali Sarkeshik; et al. (PLoS ONE, 2010)
Molecular pathways regulating rapid proliferation and persistence are fundamental for pathogens but are not elucidated fully in Toxoplasma gondii. Promoters of T. gondii ribosomal proteins (RPs) were analyzed by EMSAs and ChIP. One RP promoter domain, known to bind an Apetela 2, bound to nuclear extract proteins. Promoter domains appeared to associate with histone acetyl transferases. To study effects of a RP gene's regulation in T. gondii, mutant parasites (Δrps13) were engineered with integration of tetracycline repressor (TetR) response elements in a critical location in the rps13 promoter and transfection of a yellow fluorescent-tetracycline repressor (YFP-TetR). This permitted conditional knockdown of rps13 expression in a tightly regulated manner. Δrps13 parasites were studied in the presence (+ATc) or absence of anhydrotetracycline (-ATc) in culture. -ATc, transcription of the rps13 gene and expression of RPS13 protein were markedly diminished, with concomitant cessation of parasite replication. Study of Δrps13 expressing Myc-tagged RPL22, -ATc, showed RPL22 diminished but at a slower rate. Quantitation of RNA showed diminution of 18S RNA. Depletion of RPS13 caused arrest of parasites in the G1 cell cycle phase, thereby stopping parasite proliferation. Transcriptional differences ±ATc implicate molecules likely to function in regulation of these processes. In vitro, -ATc, Δrps13 persists for months and the proliferation phenotype can be rescued with ATc. In vivo, however, Δrps13 could only be rescued when ATc was given simultaneously and not at any time after 1 week, even when L-NAME and ATc were administered. Immunization with Δrps13 parasites protects mice completely against subsequent challenge with wildtype clonal Type 1 parasites, and robustly protects mice against wildtype clonal Type 2 parasites. Our results demonstrate that G1 arrest by ribosomal protein depletion is associated with persistence of T. gondii in a model system in vitro and immunization with Δrps13 protects mice against subsequent challenge with wildtype parasites.